Ecology and ecophysiology of Zostera capensis: responses and acclimation to temperature - Lawrence, Cloverley Mercia (Department of Biological Sciences, 2021)
This study aimed to understand the ecology of the threatened, habitat-forming seagrass, Zostera capensis in Langebaan Lagoon, a marine protected area that forms part of the West Coast national park, South Africa; and the physiological strategies that allow this habitat to persist in sub- and supra-optimal temperatures. First, the environmental drivers responsible for spatial and temporal variability in Zostera and its associated macro-epifauna were determined. Secondly, the effects of temperature and the role of algal grazing in maintaining seagrass performance under temperature stress were investigated. Seasonal field collections of seagrasses and their associated macro-epifauna were undertaken, along with regular measurements of key environmental variables. Thereafter, mesocosm experiments were performed to measure the responses of Zostera to thermal stress and grazing using morphometry, fluorometry, chromatography and biochemistry. Significant seasonal variability in seagrass distributions with severe diebacks in summer were found, which influenced associated macro-epifauna communities. Populations responded to environmental stress by changing their growth form producing small-leaves in high densities in the high intertidal, while those in low intertidal and subtidal areas produced sparse, large-leaved populations. These distinct populations supported unique faunal diversities, which were dominated by grazing invertebrates. Temperature was a consistent driver of seagrass density and leaf size, while turbidity and exposure were key environmental factors that influenced macro-epifaunal patterns. Macro-epifaunal abundances were highly positively correlated with seagrass leaf width and biomass. Different growth forms displayed different responses to thermal stress, including a higher photosynthetic rate, and accumulations of carbon and nitrogen as phenolic compounds, in small- compared to large-leaved plants. This implies that large-leaved populations are more vulnerable to stress from fouling, which was evident in their larger epiphyte loads, compared to small-leaved populations. In addition, grazers were ineffectual at regulating epiphyte growth which increased under warming conditions. These findings suggest differences in resilience between sub-populations of Zostera, and attest to their capacity to recover from environmental stress. They further emphasise the significance of identifying characteristics and acclimation strategies that allow habitats to persist under climate change, and thus sustain biodiversity and productivity, as well as continue to provide important ecosystem services.